Bail prediction: exploring the role of neighborhood context in Philadelphia - Vîlcică, E. Rely (Criminal justice and behavior, 2015)
The concurrent impact of individual and neighborhood effects on defendant pretrial performance has not been studied. This study asks whether there is neighborhood-level variation in defendants? failure to appear and pretrial crime and explores the impact of three neighborhood structural conditions (socioeconomic status, stability, and racial composition). The study was conducted in Philadelphia, Pennsylvania, on a 2005 sample of defendants (N = 800), followed for a year to record bail outcomes. Defendants? residences were geocoded within 45 neighborhoods. Census data were used for neighborhood structural characteristics. Multilevel analyses (hierarchical linear modeling) found no neighborhood variation. However, individual-level results indicate that a defendant?s neighborhood status and stability are negatively related to rearrest. Defendants from more affluent and stable neighborhoods are less likely to be rearrested for new crime. Although reliance on individual-level prediction at bail seems warranted, the study underscores the need to further explore the linkage between neighborhood conditions and pretrial outcomes.